Childhood abuse and neglect in routine care psychotherapy patients - Teismann, Tobias; Hahlweg, Kurt; Friedrich, Sören; Margraf, Jürgen (Frontiers in Psychiatry, 2025)
BackgroundChildhood maltreatment has been well established to contribute to the development and the poorer course of mental disorders across the lifespan. However, studies focusing on patients who are undergoing psychotherapy in natural settings are rare. On this background, the current study aimed to investigate (1) the prevalence of childhood maltreatment in routine care psychotherapy patients, (2) associations between childhood maltreatment and symptom severity, and (3) the influence of childhood maltreatment on treatment outcome.MethodData from N = 549 outpatients [60.3% female; age: M(SD) = 36.29 (13.47), range: 17–74 years] who received cognitive behavioral therapy at an outpatient clinic were collected. Self-report measures of childhood maltreatment, depression, anxiety, positive mental health, and treatment satisfaction were assessed before and after treatment.ResultsAny form of childhood maltreatment was reported by 57.6% of the study sample; women were more affected than men, and childhood maltreatment was associated with heightened symptom severity and lowered positive mental health. Emotional abuse was predictive of increased posttreatment depression, anxiety, and reduced positive mental health, whereas emotional neglect was predictive of lower patient-reported global treatment success—after controlling for age, gender, pretreatment depression, anxiety, and positive mental health.DiscussionChildhood maltreatment is prevalent in routine care psychotherapy patients and associated with symptom severity as well as reduced treatment response. Emotional abuse and emotional neglect exert an especially pernicious influence; particular attention must therefore be paid to these respective childhood experiences, as they can easily go unnoticed in the early phases of psychotherapy.